Morphine Does Not Affect Myocardial Salvage in ST-Segment Elevation Myocardial Infarction. - Hye Bin Gwag; Taek Kyu Park; Young Bin Song; Eun Kyoung Kim; Woo Jin Jang; Jeong Hoon Yang; Joo-Yong Hahn; Seung-Hyuk Choi; Jin-Ho Choi; Sang Hoon Lee; Yeon Hyeon Choe; Joonghyun Ahn; et al. (PLoS ONE, 2017)
Recent studies have proposed intravenous (IV) morphine is associated with delayed action of antiplatelet agents in acute myocardial infarction. However, it is unknown whether morphine results in increased myocardial damage in ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). We investigated myocardial salvage index (MSI) to determine whether IV morphine affects myocardial injury adversely in STEMI patients undergoing primary PCI. 299 STEMI patients underwent contrast-enhanced magnetic resonance imaging a median of 3 days after PCI. Infarct size was measured on delayed-enhancement imaging, and area at risk was quantified on T2-weighted imaging. MSI was calculated as '[area at risk-infarct size] X 100 / area at risk'. IV morphine was administrated in 32.1% of patients. Patients treated with morphine had shorter symptom to balloon time and higher prevalence of Thrombolysis in Myocardial Infarction flow grade 0 or 1. The morphine group showed a trend toward larger MSI and infarct size and significantly greater area at risk than the non-morphine group. After propensity score matching (90 pairs), MSI was similar between the morphine and non-morphine group (46.1% versus 43.5%, P = .11), and infarct size and area at risk showed no difference. In propensity score-matched analysis, IV morphine prior to primary PCI in STEMI patients did not cause adverse impacts on myocardial salvage.